Thermo-luminescence Response of Carbon Nanotubes and Some Other Familiar TL Materials Using Medical LINAC - Sohan, N. A.; Dewan, M. J.; Rahman, A. K. M. M.; Al-Mamun, M.; Hosan, M. I. (Journal of Scientific Research, 2020)
Strain and impurity defects in carbon nanotubes (CNTs) particularly their potentiality as a new TL material has been studied over the years. In this research, our main objective is to explore the suitability of using CNTs and its composites in the area of TL dosimeter. For this purpose, a study was carried out between the TL responses of the dosimeters TLD-100, TLD-7000 and NaI-LiF pellets. To carry out this research, equivalent irradiations were performed with these pellets using clinical linear accelerator (LINAC) under 6 MV X-ray photon beam. The dose range was from 0.5 to 5 Gy. During irradiation, the dose rate was kept constant at 300 MU/min. TLD reader was used to readout the samples in a flowing N2 atmosphere to reduce surface oxidation.During readout, pre-heat temperature was set initially at 50 °C, acquired temperature rate 10 °C/s and maximum annealed temperature was 300 °C. Response of TLD-100 under varying dose was typically linear for any doses but other dosimeters TLD-7000 showed supra-linearity beyond 2 Gy and NaI-LiF pellets showed sub-linearity response after 2 Gy. The TL glow peak of CNTs indicated that it was lying somewhere away from 300 °C.